Pengaruh Penggunaan Media Sosial (Instagram) Terhadap Prestasi Akademik Mahasiswa - Tarigan, Joy Maranatha; Soesilo, Tritjahjo Danny; Irawan, Sapto (STKIP Andi Matappa, 2019)
Social media has become one part of the society, social media users, especially students, make everyone communicate with each other and share information. This research aimed to identifying the influence of using social media (instagram) on academic achievement. The subjects of the study were the 2015 SWCU FKIP BK students. The data analysis method used was path analysis. Based on data analysis, the results obtained sig = 0.711> 0.05 so that it can be said that there is no significant effect. Data values t = 0.373 < 2.002 and the value of R Square is 0.002, according the results, the concluded that there is no significant influence between the using of social media (instagram) on academic performance because of the influence of 0.2% and 99.8% influenced by other factors not explained in this research.